2007
DOI: 10.1096/fj.06-7136com
|View full text |Cite
|
Sign up to set email alerts
|

The spinal muscular atrophy gene product regulates neurite outgrowth: importance of the C terminus

Abstract: Spinal muscular atrophy is a neurodegenerative disease accompanied by a loss of motoneurons. Either mutations or deletions in the survival of motoneuron (SMN) gene are responsible for this defect. SMN is an assembly protein for RNA-protein complexes in the nucleus and is also found in axons of neurons. However, it is unclear which dysfunctions of SMN are important for disease progression. In this study we analyzed the contributions of different SMN regions for localization and neuronal differentiation associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 64 publications
3
50
0
Order By: Relevance
“…These data indicate that the number or structural integrity of gems may not be directly relevant to SMA disease progression. Instead, other nuclear or axonal SMN functions could be responsible for motor neuron degeneration (38)(39)(40)(41)(42)(43)(44). Furthermore, only a subset of SMN molecules is bound by FGF-2 23 (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the number or structural integrity of gems may not be directly relevant to SMA disease progression. Instead, other nuclear or axonal SMN functions could be responsible for motor neuron degeneration (38)(39)(40)(41)(42)(43)(44). Furthermore, only a subset of SMN molecules is bound by FGF-2 23 (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Full-length human SMN pSMN1-294-EGFP and the mutants pSMN1-239-EGFP and pSMN235-294-EGFP were described before (43). For expression of Gemin2, a complete cDNA contained in pCMV-SPORT6 was used.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, defects in actin organization have also been observed in SMN-depleted PC12 cells. While one study demonstrated an accumulation of F-actin at the cell periphery [94], another showed a change in G-/F-actin ratio due to an increase in the F-actin component [74]. Whether the above-described defects in actin organization are directly or indirectly due to the regulation of actin mRNA still needs to be established.…”
Section: B-actin Mrna Axonal Transportmentioning
confidence: 98%
“…Interestingly, SMN expression increases in both murine neurosphere-derived neural stem cells and PC12 cells during neuronal differentiation [72,74]. Fan and Simard reported that SMN localizes in growth cones of mouse embryonal teratocarcinoma P19 cells during neuronal differentiation [70].…”
Section: Smn Function and Sma Pathology In Motor Neuronsmentioning
confidence: 99%
See 1 more Smart Citation